Experimental Study on Slender CFRP-Confined Circular RC Columns under Axial Compression - Zhongjun Hu; Quanheng Li; Hongfeng Yan; Yuchuan Wen (Applied Sciences, 2021)
The test results on the performance of carbon fiber-reinforced polymer (CFRP)-confined reinforced concrete (RC) columns under axial compression load are presented in this study. Twelve slender CFRP-confined circular RC columns with a diameter of 200 mm were divided into two groups. Six specimens with different slenderness ratios of 12, 20, 32, 40, 48, and 56 were contained in each group. The experimental results demonstrated the circumferential CFRP wrap was effective in enhancing the ultimate axial load of slender CFRP-confined circular RC columns compared with unwrapped RC columns. The experimental investigation also showed that the slenderness of the specimens had important influences on the axial compressive behavior, and the axial bearing capacity of slender CFRP-confined circular RC columns decreased as the slenderness ratio increased. In order to predict the load-carrying capacities of slender CFRP-confined circular RC columns, a formula was proposed and the prediction agreed with the experiments. The slenderness of slender CFRP-confined circular RC columns was recommended to be less than 26.5 in practical engineering.